2014
DOI: 10.4103/0976-9668.136290
|View full text |Cite
|
Sign up to set email alerts
|

Surgical correction of excessive gingival display in class I vertical maxillary excess: Mucosal strip technique

Abstract: There are several conditions that results in excessive gingival display. In case of class I vertical maxillary excess the reason for this excessive display is the hypermobile lip. Though orthodontic treatment is the choice of treatment, surgical repositioning along with the orthodontics gives more predictable and stable results. This case report discusses cosmetic surgical management of case with class I vertical maxillary excess with excessive gingival display. The technique involves removal of strip of mucos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 6 publications
0
18
0
4
Order By: Relevance
“…11 Altered passive eruption occurs when the periodontal complex does not migrate apically in the direction of the cementoenamel junction, covering part of the clinical crown, resulting in short teeth. 10 This covering may have aesthetic complications, especially in patients with a high smile line. The prevalence of gummy smile is 10% among the population aged between 20 and 30 years, and is more common among women than men 11 .…”
Section: Introductionmentioning
confidence: 99%
“…11 Altered passive eruption occurs when the periodontal complex does not migrate apically in the direction of the cementoenamel junction, covering part of the clinical crown, resulting in short teeth. 10 This covering may have aesthetic complications, especially in patients with a high smile line. The prevalence of gummy smile is 10% among the population aged between 20 and 30 years, and is more common among women than men 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Van der Geld et al 43 concluded in their study that a lip line height that exposed more than 4 mm of gingival display was considered as a Gummy Smile line. Jannani et al 46 stated that a smile is introduced as attractive when the maxillary teeth are entirely shown in addition to approximately 1 mm of gingival display. However, a gingival display not more than 2-3 mm is also contemplated as acceptable, while a disproportionate exposure (>3 mm) is basically stated as not pleasant.…”
Section: Discussionmentioning
confidence: 99%
“…The acceptable gingival exposure and the diagnosis of Gummy Smile in some previous studies is shown in Table 1. 4,5,11,[43][44][45][46]…”
Section: Discussionmentioning
confidence: 99%
“…Для усунення проблеми сьогодні застосовують чотири лікувальні опції, різні за складністю, тривалістю і підставами для застосування: техніка висічення смужки слизової оболонки (Mucosal Strip Technique) [7,8]; зменшення видимості зубів за допомогою фіксованих часткових протезів [5] або їх ортодонтичної інтрузії [15]; ортогнатична хірургія [3,4]; Стратегічна імплантація® [9,10].…”
Section: опис клінічного випадку № 2 стратегічна імплан-тація®unclassified